2004
DOI: 10.1111/j.1365-2729.2004.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Transforming teaching and learning: embedding ICT into everyday classroom practices

Abstract: Drawing on socio-cultural theory, this paper describes how teams of teachers and researchers have developed ways of embedding information and communications technology (ICT) into everyday classroom practices to enhance learning. The focus is on teaching and learning across a range of subjects: English, history, geography, mathematics, modern foreign languages, music and science. The influence of young people's out-of-school uses of ICT on inschool learning is discussed. The creative tension between idiosyncrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
112
0
18

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(131 citation statements)
references
References 10 publications
1
112
0
18
Order By: Relevance
“…In other words, the social practices of school subjects are embedded in deep understandings of the subject's knowledge regime, which co-shapes technologies more than technologies shape the subjects (Jewitt, 2006;Elf, 2014a-b). Further, the conception of subject cultures is closely related to teachers' and pupils' attitudes to and hence use of digital media in classroom practice (Goodson & Mangan, 1995;Sutherland et al, 2004;Selwyn, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the social practices of school subjects are embedded in deep understandings of the subject's knowledge regime, which co-shapes technologies more than technologies shape the subjects (Jewitt, 2006;Elf, 2014a-b). Further, the conception of subject cultures is closely related to teachers' and pupils' attitudes to and hence use of digital media in classroom practice (Goodson & Mangan, 1995;Sutherland et al, 2004;Selwyn, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This does not necessarily mean the Net Generation can make full use of ICT for teaching and learning (Katz, 2007). Studies have indicated that ICT can enhance teaching and learning in different disciplines (Anderson, 2008;Grabe & Grabe, 2007;Sutherland, Armstrong, Barnes, Brawn, Breeze, Gall, Matthewman, Olivero, Taylor, Triggs, Wishart, & John, 2004;Wong, Quek, Divaharan, Liu, Peer, & Williams, 2006). For these reasons, most curriculum documents state the importance of ICT and encourage school teachers to use them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet ICT can improve efficiency (McCormick, Scrimshaw 2001:45) or be "added" to other features of a subject as an "extension" (McCormick & Scrimshaw 2001:45). Moreover, digital media can be "embedded" in a deeper way in different parts and contents of the subject, which may also imply that the fundamental nature of the subject will change (Sutherland et al 2004).…”
Section: The Use Of Ict In Schoolmentioning
confidence: 99%
“…School subject paradigms are important with regard to the use of ICT (Goodson & Mangan 1995, Sutherland, Armstrong, Barnes, Brawn, Breeze, Gall et al 2004). Digital media's entry into education can be conceived as filled with tension (Hennessy, Ruthven, Brindley et al 2005, John 2005.…”
Section: The Use Of Ict In Schoolmentioning
confidence: 99%